Impelementasi Alat Teknologi Dalam Novel Matahari Karya Tere Liye - Ramadhan, Fajar; Aqsha Pasalewa Kusumojakti, Mochamad; Dwi Kurniawan, Eva (Jurnal Manajemen, Ekonomi, Hukum, Kewirausahaan, Kesehatan, Pendidikan dan Informatika, 2023)
The novel Matahari by Tere Liye is a literary work that describes emotional stories and the main character's journey through various events. However, it is not only the story and characters that attract attention, but also the technological devices used in this novel. This journal aims to analyze the use of technological devices used in stories. The method used uses a hermeneutical approach. The results of the analysis show that the hermeneutic approach provides deeper insight into how technology is used as a narrative tool in the novel. With this approach, research can explore the deeper meaning of each scene involving technology, as well as how the use of technology affects character development and storyline. In this way, we can gain a deeper understanding of the role of technology in the story and how it reflects broader social and cultural aspects of modern society.